Cerdas Bermedia Sosial dan Produktif Bagi Ibu Rumah Tangga Melalui Pelatihan Digital Marketing - Kaslam, Kaslam; Luneto, Riska; Aisyah, Andi Annur; Rahmadani, Nurul Huda (Ruang Komunitas : Jurnal Pengabdian Masyarakat, 2023)
The use of the internet to market products or known as digital marketing, is currently growing very rapidly. The level of usage is in line with the presence of smartphones at very affordable prices. However, its use is actually not optimal because it is only used for social media which is not productive. Even though it can be used in entrepreneurship, especially among housewives, so that their time is more efficient. This community service activity was carried out in the form of training for 20 housewives who already have businesses, in Moncongloe Village, Maros Regency, with the theme "Smart Social Media and Productive". After participating in digital marketing training, participants are expected to be able to understand digital marketing and apply it so that they can optimally increase business marketing effectiveness, be able to create a more cost-effective digital brand image. After the training was carried out, the participants knew how to use social media to market their products as well as some tips given to be able to boost product sales.